A Comprehensive Pan-Cancer Analysis of the Tumorigenic Role of Matrix Metallopeptidase 7 (MMP7) Across Human Cancers - Meng, Nana; Li, Yaguang; Jiang, Pengcheng; Bu, Xuefeng; Ding, Jifei; Wang, Yan; Zhou, Xiaodong; Yu, Feng; Zhang, Yongjun; Zhang, Jie; Xia, Leizhou (Frontiers in Oncology, 2022)
Growing evidence has shown the oncogenic function of matrix metallopeptidase 7 (MMP7) in various tumors. However, no systemic pan-cancer analysis on the association between MMP7 and different cancers based upon big clinical data is available. TIMER2, GEPIA2, UALCAN, cBioPortal, String, Metascape, and other web databases were searched in the present study. Generally, MMP7 expression is significantly upregulated in most The Cancer Genome Atlas (TCGA) cancer types compared to the paired normal controls, yet is downregulated in tumor tissues of invasive breast carcinoma (BRCA), kidney chromophobe (KICH), kidney renal clear cell carcinoma (KIRC), liver hepatocellular carcinoma (LIHC), and skin cutaneous melanoma (SKCM). MMP7 protein expression is notably higher in the primary tumor tissues of colon cancer, lung adenocarcinoma (LUAD), and uterine corpus endometrial carcinoma (UCEC) than in the normal tissues and is significantly lower in the primary tumor tissues of breast cancer, clear cell renal carcinoma, and ovarian cancer. Furthermore, MMP7 expression is strongly associated with pathological stages, clinical outcomes, tumor mutational burden (TMB), and microsatellite instability (TSI). Gene amplification was detected in most TCGA cancer types. In addition, the missense mutation is the primary type of MMP7 genetic alteration in tumors. Significant positive correlations between MMP7 expression and cancer-associated fibroblasts (CAFs) have been demonstrated in most TCGA cancers. MMP7 expression was also found to positively correlated with infiltration of dendritic cells and macrophages in some specific tumor types. Functional enrichment analysis by Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways and gene ontology (GO) methods revealed that RNA processing and DNA damage checkpoints might reveal the pathogenetic mechanisms of MMP7. This pan-cancer analysis provides a clear panorama for the tumorigenic roles of MMP7 across different cancer types. Moreover, MMP7 could be a potential drug therapeutic target in such cancers.